A efetivação do direito à convivência familiar da criança migrante indocumentada como máxima de Direitos Humanos e o primado da fraternidade - Mauricio Cleber Miglioranzi Santos (2025)
Brazil, with its vast land borders shared with numerous South American countries, experiences significant migratory flows, particularly in twin cities where only a street often separates nations. Since 2015, migration issues have gained increased visibility, especially with the influx of Venezuelan migrants into Pacaraima, Roraima. This migration has strained local and federal resources, highlighting the extreme vulnerability of migrant children and adolescents. These minors, already facing the severe challenges that drive migration, also suffer from a lack of documentation, which often leads to measures that hinder the maintenance or restoration of family ties. This study focuses on the situation in the State Justice Court of Corumbá-MS, a border town with Bolivia, where cases of undocumented children separated from their families are frequent. The research, situated within the field of Human Rights, State, and Border Studies, employs a descriptive and exploratory methodology, including a literature review and data collection from the Juvenile Court of Corumbá-MS. The study aims to understand the existing legal framework and the care provided to this vulnerable population, with a focus on preserving the right to family life as a fundamental human right, underpinned by the principle of fraternity.